Pelatihan Menggunakan Canva Untuk Meningkatkan Kreatifitas Design Grafis Pada Madrasah Ibtidaiyah Al-Khoiriyah.: Pelatihan Menggunakan Canva Untuk Meningkatkan Kreatifitas Design Grafis Pada Madrasah Ibtidaiyah Al-Khoiriyah. - Nawangsih, Ismasari; Purnamasari, Pupung; Maulana, Donny; Maulana Majid, Annisa; Budiarto, Eko; Tri Pranoto, Gatot (DPPM Universitas Pelita Bangsa, 2024)
The development of creativity and teaching and learning activities for students and teachers in the world of education continues to develop along with the times. The digital era is supported by various application devices and the existence of the internet currently helps the teaching and learning process. Students need Canva training as a promotional media and information on school activities. The uses for students are making posters, class presentations and so on. Meanwhile, for teachers, it is a teaching presentation. This training is assisted and supported by the Lecturer Team as tutors because community service activities are part of the tri dharma of lecturers which must be carried out as a form of service and concern for the surrounding community. Activities in the form of counseling and design training using Canva were carried out at Madrasah Ibtidaiyah Al Khoiriyah. The target group for this PKM activity is 20 students and 2 teachers. This activity is carried out face to face (On the spot training) which begins with observation and coordination and permission with the local school principal regarding planned activities to be carried out in that environment regarding availability. place, time and participants. Service activities are carried out using several stages: Preparation stage; Stage of implementing socialization regarding digital content for school students. The method used in implementing PKM activities is socialization using counseling techniques in the form of lectures or presenting material in the form of theory and videos related to the theme we are taking, questions and answers, creations and games. The results of the activity show an increase in creative ways of learning for students